Effects of individual performance on humanitarian operations performance in humanitarian organisations in Malaysia - Mat Jusoh, Zeti Suzila; Hassan, Mazlan; Abdullah, Abdul Rashid; Hashim, Haslinda; Irfan, Muhammad (Academia Industry Networks, 2021)
The purpose of this study is to assess the effects of individual performance on humanitarian operations performance in Malaysia’s humanitarian organisations. A cross-sectional survey across Malaysia yielded 593 valid responses. The sample was restricted to respondents registered with the National Disaster Management Agency (NADMA). Smart PLS version 3.0 was employed to assess the proposed reflective-formative model through path modelling and bootstrapping techniques. The results show that individual performance is positively related to humanitarian operations performance. This paper provides empirical evidence on the positive effects of individual performance on humanitarian operations performance from the perspective of humanitarian organisations in Malaysia.